Kinerja Dewan Perwakilan Rakyat Daerah Kabupaten Buton - Wa Ode Usnia (Program Studi Ilmu Administrasi Negara, Program Pascasarjana, Universitas Dayanu Ikhsanuddin, Baubau, 2022)
This study aimed to describe the performance of the Buton Regional House of Representatives. The study used qualitative methods with a case study approach. Data collection was done through observation, interviews, literature studies and documentation. Data analysis used descriptive analysis which emphasized more on the analysis of the process of inductive inference and analysis of the dynamics of the relationship between observed phenomena. The results of the study showed that quantity: Quantity in the legislative function, namely the number of draft regulations per year that had been discussed by members of the Regional People's Representative Council in 2017 as many as 11 local regulations and complaints in 2017 as many as 20 proposals for complaints that were resolved 16 complaints. The quantity in the budgeting function, that was, every public complaint about the budget was carried out when the members of the Regional People's Legislative Assembly held a recess so that the community understood the regional budget in Buton Regency. Draft Regional Regulations concerning Amendments to the Regional Revenue and Expenditure Budget for the 2018 budget year had been stipulated as Regional Regulations. Determination was carried out during the Plenary Meeting with the District Level Talks on the Draft of the Buton Regency Regional Regulation concerning Amendments to the Regional People's Representatives Council. The quantity in the supervisory function was the amount of supervision carried out by the board members every time they carried out activities held every 2 times a year, supervisory activities carried out by board members in absorbing community demands such as complaints from the community regarding delays in the election of village heads. appoint executive village heads who would carry out their duties until 2020. Quality was: Quality in the legislative function, namely the ability of Buton District council members to absorb community aspirations had been carried out in accordance with the functions of the legislature that accommodated community input and criticism in the implementation of development, community and government in the area. The quality of the budget function was to accommodate the people's aspirations, especially in budget matters by capturing the aspirations of the people in their respective Electoral Districts, because each board member must have his constituents who must be considered of course striving for the Electoral District to get an annual budget allocation The quality of the supervisory function was that board members had a role in accepting and following up on community aspirations, apart from the existence of the Community Aspiration Recipient Special Committee. Members of the faction were very open space for the community to participate in the framework of decision making.